2013
DOI: 10.1148/radiol.13121362
|View full text |Cite
|
Sign up to set email alerts
|

Common Pediatric Cerebellar Tumors: Correlation between Cell Densities and Apparent Diffusion Coefficient Metrics

Abstract: Negative correlation was found between cellularity and ADC metrics of common pediatric cerebellar tumors. Although ADC metrics are useful in the preoperative diagnosis of common pediatric cerebellar tumors and this utility is generally attributed to differences in cellularity of tumors, tumor cellularity may not be the sole determinant of the differences in diffusivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 11 publications
3
45
0
1
Order By: Relevance
“…Differences in diffusion properties of low‐ and high‐grade tumors are caused by several factors including different tumor cellularity and nucleus to cytoplasm ratio. In contrast to high‐grade tumors, low‐grade tumors are characterized by hypocellularity, low nucleus to cytoplasm ratio, and large extracellular spaces, which is typically represented by high MD/ADC values …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in diffusion properties of low‐ and high‐grade tumors are caused by several factors including different tumor cellularity and nucleus to cytoplasm ratio. In contrast to high‐grade tumors, low‐grade tumors are characterized by hypocellularity, low nucleus to cytoplasm ratio, and large extracellular spaces, which is typically represented by high MD/ADC values …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies used quantitative apparent diffusion coefficient (ADC) measurements to differentiate the various grades and histological subtypes of cerebellar tumors. ADC values were typically measured in the solid, contrast enhancing component of the tumor (SCT) . This approach, however, has several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Jenkinson et al have reported no correlation between the ADC metrics and cellularity in oligodendrogliomas 35 . Additionally, Koral et al have shown that although ADC metrics are useful in the preoperative diagnosis of common pediatric cerebellar tumors, however tumor cellularity may not be the sole determinant of the differences in diffusivity 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Apparent diffusion coefficient (ADC) maps were generated by fitting the DWI signal to a mono-exponent on a pixel-by-pixel basis 25, 26 , using VnmrJ software.…”
Section: Methodsmentioning
confidence: 99%
“…Since QSI is very sensitive to changes in tissue microstructure, QSI may be an efficient method to noninvasively evaluate the HG of CRC. Prior studies have reported that it is often problematic to discriminate between the HGs of tumor based only on ADC values because of the sizable overlap between the ADC values of different HGs of tumor . Thus, QSI may be a more accurate method than conventional DWI to discern the HG of CRC.…”
Section: Discussionmentioning
confidence: 99%